2010
DOI: 10.1097/bpo.0b013e3181d98f2c
|View full text |Cite
|
Sign up to set email alerts
|

Eleven Years Experience in the Operative Management of Pediatric Forearm Fractures

Abstract: Level III, Retrospective Comparative Study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
201
3
33

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(254 citation statements)
references
References 29 publications
17
201
3
33
Order By: Relevance
“…How much malreduction is acceptable has always been a matter of great debate. As mentioned in literature, angular deformity >10° and complete displacement account for unacceptable reduction [6,12]. Also, younger children tend to tolerate greater deformity much better than older ones due to better remodelling potential [1,[13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…How much malreduction is acceptable has always been a matter of great debate. As mentioned in literature, angular deformity >10° and complete displacement account for unacceptable reduction [6,12]. Also, younger children tend to tolerate greater deformity much better than older ones due to better remodelling potential [1,[13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…To minimize angular deformity, maintain anatomical position, and preserve rotation of forearm, operative management has become increasingly popular for pediatric diaphysis forearm fractures. [4,13] Our study showed a significant high proportion (93.3%, N=60, p<0.001) of male children with both bone fracture of forearm. This may be due to the fact that male children are more involved in outdoor and playful activities like climbing trees.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, another study by Flynn JM. et al [13] reported excellent outcome in 77.7%, and another by Parajuli NP. et al [19] reported excellent outcomes in 94% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations